1995
DOI: 10.1039/p19950001775
|View full text |Cite
|
Sign up to set email alerts
|

3′,4-Di-O-methylcedrusin: synthesis, resolution and absolute configuration

Abstract: The title compound has been synthesised in racemic form by a biomimetic reaction sequence. The two enantiomers were resolved by column chromatography of one of the synthetic intermediates. On the basis of CD results a tentative absolute configuration for the synthetic enantiomers and natural 3',4-di-0methylcedrusin is proposed.Sungre de drug0 (dragon's blood), a blood-red latex produced by various South American Croton species, is widely used in local medicine for its wound-healing properties and as an antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…The absolute configuration of 2 was determined by analysis of its CD spectrum, where the CD curve with negative Cotton effects at λ max 241 and 293 nm was similar to that of (7R,8S)-4-O-methyldihydrodehydrodiconiferyl alcohol. 27) Consequently, the absolute stereochemistry of C-7 and C-8 were R and S, respectively and compound 2 was identified as (7R,8S)-dihydrodehydrodiconiferyl alcohol 4-β-D-xyloside.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute configuration of 2 was determined by analysis of its CD spectrum, where the CD curve with negative Cotton effects at λ max 241 and 293 nm was similar to that of (7R,8S)-4-O-methyldihydrodehydrodiconiferyl alcohol. 27) Consequently, the absolute stereochemistry of C-7 and C-8 were R and S, respectively and compound 2 was identified as (7R,8S)-dihydrodehydrodiconiferyl alcohol 4-β-D-xyloside.…”
Section: Resultsmentioning
confidence: 99%
“…2). The absolute structures of many dihydrobenzo[b]furan-type neolignans have been assigned 21,[40][41][42][43] on the basis of the CD results of Achenbach et al 44) However, Antus et al 45) re- …”
Section: Resultsmentioning
confidence: 99%
“…Lemiere et al reported that the configurations at C-7 and C-8 of the dihydrobenzofuran skeleton can be distinguished in the range of 220-240 nm by CD spectroscopy. 18) We reported the CD evidence of (Ϫ)-e-viniferin and its oxidative derivative [(2R,3R)-3-(3,5-dihydroxyphenyl)-6-hydroxy-2-(4-hydroxyphenyl)-2,3-dihydrobenzofuran-4-carbaldehyde: 39] [negative Cotton effect at 236-237 nm].…”
Section: Chemical Constituents In the Leaves Of Vateria Indicamentioning
confidence: 99%